The majority of type 2 diabetic patients in Finnish primary care are at very high risk of cardiovascular events: A cross-sectional chart review study (STONE HF). Issue 1 (February 2022) - Metsärinne, Kaj; Pietilä, Mikko; Kantola, Ilkka; Stenman, Lotta K.; Hätinen, Olli-Pekka; Vesikansa, Aino; Poussa, Tuija; Niskanen, Leo; ,
Highlights: Over 60% of primary care T2D patients were at very high risk of cardiovascular events. DKD was underdiagnosed even when eGFR and albuminuria were measured. Routine screening of albuminuria and systematic diagnosis of HF require more focus. The use of treatments with proven cardioprotective effects is currently suboptimal. Abstract: Aims: To characterize clinical profiles, prevalence of chronic kidney disease (CKD), and treatment patterns in type 2 diabetes (T2D) and heart failure (HF) patients in Finnish primary care. Methods: A total of 1385 patients (1196 with T2D, 50 with HF, and 139 with T2D and HF) in 60 Finnish primary care centers were recruited to this cross-sectional study. Data on demographic and clinical characteristics, laboratory measurements, and medications were collected retrospectively from medical records. T2D patients were classified according to their risk of cardiovascular (CV) events as very high-risk (62%) and other patients (38%). Results: Of the T2D patients, 10% (139/1335) had a diagnosis of HF and 42% (457/1090) had stage 3–5 CKD and/or albuminuria based on laboratory measurement. Of the HF patients, 74% (139/189) had T2D and 78% (114/146) had stage 3–5 CKD and/or albuminuria. Metformin was the most frequently used medication in both very high-risk patients (74%) and other patients (86%). SGLT2 inhibitors and/or GLP-1 analogues were used by 37% of very high-risk patients compared to 42% in other patients. Conclusions: The majority of T2D patients in Finnish primary care are at very high risk of cardiovascular events. However, the implementation of treatments with proven cardioprotective effects in very high-risk patients is currently suboptimal.